(untitled) (Research, Society and Development, 2018)
Cabotage is a constant aspect of cargo transportation, both in Brazil and in the world. It exposes an energy efficiency if we draw the fuel versus tonnage ratio, it is environmentally sustainable by the CO2 emission reduction on the roads, when compared to road modes, it presents load safety, with this the cabotage is becoming a key factor of competitiveness between the companies. From this, this present study proposes the analysis of the enlargement of the cabotage routes of the Pulp and Paper Company in question, with the creation of a new concept of cargo transportation, based on the available official literature and internally identified know-how in the company studied. As for the characterization of the most feasible Routes for the transport of paper by cabotage, and the composition of freight costs for the studied routes, a data collection was performed, using the unstructured interview, technical visits, and observation. They were involved in the areas of logistics, and logistic supplies of the company in question, to guide the research. Thus, by consolidating the information and by means of a critical look at the current situation of cabotage in Brazil and the increase of the use of the same in the company in question, it is possible to say that even being in a country unbalanced in relation to the transport matrix, the investment and increase of cabotage at the national level is very advantageous.